Industri Bordir W&R Di Nagari Cupak Kecamatan Gunung Talang Kabupaten Solok (1980-2022) - Triana Andini Putri; Etmi Hardi (Jurnal Kronologi, 2022)
This study discusses the history of the embroidery industry (1980-2022). The research problem is formulated as follows: 1). How was the development of the W&R embroidery industry in Nagari Cupak, Gunung Talang District, Solok Regency in 1980-2022. 2). How did the W&R embroidery industry strategy develop its embroidery business from 1980-2022. This writing aims to reveal the history of the W&R embroidery industry in Nagari Cupak, Gunung Talang District, Solok Regency in 1980-2022. This research using the historical writing method which consists of four stages, namely heuristics, criticisms sources, interpretations, and historiography. The results of the study that; Mrs. Yulidar's first time as an embroidery seamstress was in Nagari Cupak. Started pioneering embroidery business because of the culture of using tikuluek for women in Nagari Cupak. Second, the development of the W&R embroidery industry from its inception in 1908 until now is still ongoing, where previously a housewife changed her profession to become an embroidery owner. Even the embroidery business belonging to Mrs. Yulidar was passed on to her children to her granddaughter. Third, the development of embroidery has a promising prospect value. The marketing strategy has also been to various regions and abroad. The uniqueness of tikuluek has a traditional aesthetic but still exists and is maintained in the modern era. Keywords: Embroidery Industry, Tikuluek embroidery Abstrak Penelitian ini membahas mengenai sejarah industri bordir (1980-2022). Permasalahan penelitian ini dirumuskan sebagai berikut: 1). Bagaimana perkembangan industri bordir W&R di Nagari Cupak Kecamatan Gunung Talang Kabupaten Solok pada tahun 1980-2022. 2). Bagaimana strategi industri bordir W&R mengembangkan usaha bordirnya sejak tahun 1980-2022. Penulisan ini bertujuan untuk mengungkapkan sejarah industri bordir W&R di Nagari Cupak Kecamatan Gunung Talang Kabupaten Solok pada tahun 1980-2022. Penelitian inimenggunakan metode penulisan sejarah yang terdiri dari empat tahapan, yaitu heuristik, kritiksumber, interpretasi, dan historiografi. Hasil penelitian bahwa; pertama Ibu Yulidar sebagai penjahit bordir pertama kali di Nagari Cupak. Mulai merintis usaha bordir karena budaya pemakaian tikuluek bagi perempuan di Nagari Cupak. Kedua, perkembangan industri bordir W&R dari awal berdiri tahun 1908 hingga sekarang masih tetap berjalan, yang sebelumnya seorang ibu rumah tangga beralih profesi menjadi pemilik bordir. Bahkan usaha bordir milik Ibu Yulidar di teruskan kepada anak hingga cucu perempuannya. Ketiga, pengembangan bordir memiliki nilai prospek yang cukup menjanjikan. Strategi pemasarannya juga sudah ke berbagai daerah dan luar negeri. Keunikan tikuluek memiliki estetika tradisional tetapi masih eksis dan dipertahankan di era modern. Kata kunci: Industri Bordir, Tikuluekbordir